The Recruitment Matrix. Issue 1 (2nd January 2016) - Heritage, John
ABSTRACT: This article discusses Kendrick and Drew's (2016/this issue) conceptualization of recruitment. It is argued that the critical feature of recruitment as a category is its focus on forms of local, here-and-now assistance, which gives recruitment actions a different suite of affordances and constraints than actions soliciting assistance on some future occasion disjoined from the present. It is suggested that these latter actions must be "language heavy" and may be likely to involve heavier impositions than the aims for which recruitment generally functions, thus justifying an enhanced focus on linguistic structure and sequence. Data are in American English.